Investerings- en aanvangstoelae : 'n teoretiese en empiriese studie - Mostert, F. J.(Frederik Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D.Comm.) -- Universiteit van Stellenbosch, 1983.